How many manuscripts should I peer review per year? - Fernando Fernandez-Llimos; Teresa M. Salgado; Fernanda S. Tonin (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Peer review provides the foundation for the scholarly publishing system. The conventional peer review system consists of using authors of articles as reviewers for other colleagues' manuscripts in a collaborative-basis system. However, authors complain about a theoretical overwhelming number of invitations to peer review. It seems that authors feel that they are invited to review many more manuscripts than they should when taking into account their participation in the scholarly publishing system. The high number of scientific journals and the existence of predatory journals were reported as potential causes of this excessive number of reviews required. In this editorial, we demonstrate that the number of reviewers required to publish a given number of articles depends exclusively on the journals' rejection rate and the number of reviewers intended per manuscript. Several initiatives to overcome the peer review crises are suggested.